การอนุรักษ์อาคารก่ออิฐที่ได้รับอิทธิพลจากอาณานิคมฝรั่งเศสในชุมชนบ้านท่าแร่ จังหวัดสกลนคร, Conservation of Brick Buildings Influenced by French Colonies in Ban Tha Rae Community of Sakon Nakhon Province - พัฒนานุโรจน์ ปกรณ์ (Asian Creative Architecture, Art and Design, 2018)
Abstract This article is to study architectural styles and decorative patterns of building and propose a conservative guidance for French colonial buildings in Ban Tha Rae community. Four steps of the research methods were adopted as follows, 1) a study of an immigration and an influence of Vietnamese artwork on brick masonry buildings in Ban Tha Rae community, 2) surveying 5 brick buildings to collect physical data, 3) an analysis of the data in accordance with on-site survey and the building conservation theory and 4) meeting with local community to propose conservation guideline. This study founded that the five brick buildings were completely influenced by the French colonialists conveyed by Vietnamese technician, adapting colonial style with contexts and becoming local architecture style. In terms of architectural structure of studied buildings, the brick-wall was mainly used as load-barring structure. The upper floor and roof structure were made of hardwood. The distinctive identity of the buildings are the terrace columns with arches. The stucco was not only used for decorative purpose but for representing spiritual meaning of Christianity. For conservative concern, four of brick-buildings should be initially reinforced and repaired damaged parts and modify functions without decreasing values of the building. For another brick building, aged over 110 years old with a partial damaged wall and no roof structure, should be reconstructed in relation to old architectural evidences, gathered by researcher and local community. However, this study is only the proposed plan used as basic data for further implementations. It is suggested that further studies of local cultural issues should be added. So, the local community will be ready for being knowledge center, for architecture, arts, and local culture, as tourist connecting to other tourist networks in Sakon Nakhon province. Keywords: French Colonial Buildings, Ban Tha Rae Community, Vietnamese Technician, Brick Building Construction